HUBUNGAN STRES DENGAN INDEKS MASSA TUBUH PADA SISWA KELAS 3 SMK PENERBANGAN NASIONAL BATAM - Rusdani; Rini Susanti (Universitas Batam, 2022)
Stress is one of the responses of the body and mind's balance to change. One of the age groups susceptible to stress is adolescents. In general academic problems are the main source of stress for students. Stress if left unmanaged, can cause severe psychological and metabolic consequences. Psychological stress is often associated with increased food consumption, especially in consuming high-fat foods. Stress can also change overall food intake, such as lack or excess according to the severity of stress.Observational analytic research with cross sectional approach that done in Batam National Flight Vocational School in 2019. The sampling method is total sampling with a sample of 39 students in grade 3. The collected data were analyzed using the Kolmogorov-smirnov test with a significance level of α = 0.05.The results of this study found that the stress that dominates in this study is the mild stress category of 20 respondents (51.3%) in 3ird grade students of Batam National Aviation Vocational School. Whereas the most dominating body mass index results in this study were the Overweight-Obesity category of 21 respondents (53.8%) in the 3rd grade students of Batam National Aviation Vocational School. The Kolmogorov-smirnov test results obtained a value (p = 0.001), H0 was rejected and Ha was accepted.Based on this research result, researcher conclude that there is a significant correlation between the correlation of stress with bodyy mass index in class 3 student of Batam National Flight Vocational School in 2022.